The LYMFASIM Simulation Program for Modeling Lymphatic Filariasis and its Control - Plaisier, A. P.; Subramanian, S.; Das, P. K.; Souza, W.; Lapa, T.; Furtado, A. F.; Van der Ploeg, C. P. B.; Habbema, J. D. F.; van Oortmarssen, G. J. (Methods of Information in Medicine, 1998)
The LYMFASIM modeling framework for the transmission and control of the tropical parasitic disease lymphatic filariasis is described and its use in the context of an endemic community in north-eastern Brazil is illustrated. Lymphatic filariasis is a disease with a complex natural history with many unknowns. This complicates decision making with respect to control strategies. With LYMFASIM, a variety of hypotheses can be tested about the life history of the parasite Wuchereria bancrofti, its transmission from man to man through mosquitoes, the role of the immune system in regulating parasite numbers, the development of disease symptoms, and the effects of control measures (drug treatment or mosquito control). The implications of alternative assumptions and uncertainty about the quantification of parameters for the effectiveness of control strategies can be investigated. Thanks to the use of stochastic microsimulation, LYMFASIM is highly flexible and can be adapted and extended as new knowledge emerges.
Keywords: Lymphatic Filariasis; Tropical Disease; Simulation; Modeling; Decision Making